Rehabilitation of the multiple injured patient with spinal cord injury: A systematic review of the literature. Issue 11 (November 2019) - Christodoulou, V.N.; Varvarousis, D.; Theodorou, A.; Voulgaris, S.; Beris, A.; Doulgeri, S.; Gelalis, I.; Ploumis, A.
Abstract: Introduction: Patients with multiple injuries including spinal cord injury (SCI) have low survivability. Little is known for the effect of SCI in their rehabilitation process. Purpose: To define differences in characteristics and outcomes during the rehabilitation of multiple injured patients with SCI compared to other polytrauma patients. Materials and methods: Electronic libraries provided 425 relevant articles. Applying the criteria, 6 articles were eligible for inclusion in this review. Results: The extracted data show that multiple injured patients with SCI have an increased length of stay (LOS) in rehabilitation. Initial functional levels, as also one- and two-years follow-up are also decreased. Similar results were found comparing SCI patients with or without multiple injuries: SCI patients with multiple injuries have an increased LOS and decreased functional levels compared with SCI patients. Finally, there was nota relevance between the circumstances of the injuries, like acts of terror, and the expected rehabilitation outcome. Conclusion: Due to the rarity of eligible articles and the lack of homogenous accessing tools, a meta-analysis was not possible. There is a lack of a universal evaluation strategy or tool, for the severity of the multiple injured patients aiming at the rehabilitation outcome prognosis. Multiple-injured patients with SCI have longer rehabilitation LOS and functional outcomes compared to other polytrauma patients. Prospective studies are needed for evaluation of the differences according to the severity and the complexity of the injuries and the rehabilitation outcome depending on different rehabilitation methods and strategies.